LA VIOLENCIA NOTICIOSA: ANÁLISIS DESDE LA AGENDA-SETTING Y LAS MASCULINIDADES EN EL PROGRAMA RADIOFÓNICO PANORAMA SIN RESERVAS. - OLARTE RAMOS, CARLOS ARTURO; CARRERA RUIZ, ROBERTO; VALDEZ RUIZ, ROCÍO MONTSERRAT (CONfines de Relaciones Internacionales y Ciencia Política)
This article presents an approach to the journalistic information about acts of violence broadcasted on the political radio program Panorama Sin Reservas, produced in the Mexican state of Tabasco, with the objective of explaining the relationship between violence and hegemonic practices of masculinity. For this purpose, the newscast was monitored during the period February-March 2022, through the review of the information summary and the complete recording of the program. Once the news on violence were identified, a content analysis was carried out to, on the one hand, determine the journalistic treatment from the agenda-setting, and on the other, identify the relationship with male gender mandates. The results indicate that issues such as feminicide and homicide were high-profile topics that were made known to the audience in Tabasco, which reflect hegemonic discourses of masculinity. It is concluded that radio as a means of communication disseminates practices of violence turned into news, which even though they transmitted for informative purposes, it represents a reference for violation of human rights. It is suggested to produce investigative journalism to provide a multidisciplinary treatment to the issue of violence, which allows greater awareness of the population regarding this phenomenon and professionalization on gender for an inclusive and precise management of the issue by the media.